Delineating the age-related attenuation of vascular function: Evidence supporting the efficacy of the single passive leg movement as a screening tool - Hydren, Jay R.; Broxterman, Ryan M.; Trinity, Joel D.; Gifford, Jayson R.; Kwon, Oh Sung; Kithas, Andrew C.; Richardson, Russell S. (Journal of applied physiology (1985), 2019)
Continuous passive leg movement (PLM) is a promising clinical assessment of the age-related decline in peripheral vascular function. To further refine PLM, this study evaluated the efficacy of a single PLM (sPLM), a simplified variant of the more established continuous movement approach, to delineate between healthy young and old men based on vascular function. Twelve young (26 ± 5 yr) and 12 old (70 ± 7 yr) subjects underwent sPLM (a single passive flexion and extension of the knee joint through 90°), with leg blood flow (LBF, common femoral artery with Doppler ultrasound), blood pressure (finger photoplethysmography), and leg vascular conductance (LVC) assessed. A receiver operator characteristic curve analysis was used to determine an age-specific cut score, and a factor analysis was performed to assess covariance. Baseline LBF and LVC were not different between groups ( P = 0.6). The high level of covariance and similar predictive value for all PLM-induced LBF and LVC responses indicates LBF, alone, can act as a surrogate variable in this paradigm. The peak sPLM-induced increase in LBF from baseline was attenuated in the old (Young: 717 ± 227, Old: 260 ± 97 ml/min, P < 0.001; cut score: 372 ml/min), as was the total LBF response (Young: 155 ± 67, Old: 26 ± 17 ml, P < 0.001; cut score: 58 ml). sPLM, a simplified version of PLM, exhibits the prerequisite qualities of a valid screening test for peripheral vascular dysfunction, as evidenced by an age-related attenuation in the peripheral hyperemic response and a clearly delineated age-specific cut score. NEW & NOTEWORTHY Single passive leg movement (sPLM) exhibits the prerequisite qualities of a valid screening test for peripheral vascular dysfunction. sPLM displayed an age-related reduction in the peripheral hemodynamic response for amplitude, duration, initial rate of change, and total change with clearly delineated age-specific cut scores. sPLM has a strong candidate variable that is a simple single numeric value, for which to appraise peripheral vascular function, the 45-s hyperemic response (leg blood flow area under the curve: 45 s).